2021
DOI: 10.3389/fphar.2021.760215
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin-Based Oxygen Carriers: Potential Applications in Solid Organ Preservation

Abstract: Ameliorating graft injury induced by ischemia and hypoxia, expanding the donor pool, and improving graft quality and recipient prognosis are still goals pursued by the transplant community. The preservation of organs during this process from donor to recipient is critical to the prognosis of both the graft and the recipient. At present, static cold storage, which is most widely used in clinical practice, not only reduces cell metabolism and oxygen demand through low temperature but also prevents cell edema and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 110 publications
0
19
0
Order By: Relevance
“…Another method is to use oxygen carriers, especially those based on Hemoglobin-based oxygen carriers (HBOCs). HBOCs were originally studied as blood substitutes, but now they have been extended to the treatment of ischemia and hypoxia (Cao et al, 2021). Recently, the "repositioning" of HBOCs has led to its successful application in organ perfusion fluid, which is considered as an alternative method to improve oxygen supply and protect the optimal metabolic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another method is to use oxygen carriers, especially those based on Hemoglobin-based oxygen carriers (HBOCs). HBOCs were originally studied as blood substitutes, but now they have been extended to the treatment of ischemia and hypoxia (Cao et al, 2021). Recently, the "repositioning" of HBOCs has led to its successful application in organ perfusion fluid, which is considered as an alternative method to improve oxygen supply and protect the optimal metabolic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Hemoglobin-based oxygen carriers (HBOCs) may now be mechanically perfused in vitro at room temperature, according to research. Using HBOCs to preserve organs in vitro may have the following potential advantages: effective preservation of cell metabolism and reduction of hypoxia-induced damage, the diameter is significantly smaller than that of red blood cells to more effectively carry oxygen, without immunological response, lengthy storage time and good stability, broad tolerance for temperature, readily available from a variety of sources (Cao et al, 2021). In this study, polymerized porcine hemoglobin (pPolyHb) was used as the oxygen carrier during NMP perfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Use of HBOCs can, therefore, cause methemoglobinemia and vasoconstriction both in vitro and in vivo. 134 This may be less relevant for recipients of organs undergoing ex situ perfusion, as methemoglobin should largely be washed out of the graft before transplantation.…”
Section: Solutions For Mp Preservationmentioning
confidence: 99%
“…The factors responsible for HBOCs mediated vasoconstriction include nitric oxide (NO) scavenging, increased ET production, shear stress, and vessel wall hyperoxygenation. Safety and efficacy of HBOCs was explored using numerous preclinical and clinical studies and a HBOCs product, HBOC-201 is approved for surgical patients with acute anemia and has been available in South Africa since 2001 [134]. However, a metaanalysis of cell-free hemoglobin-based blood substitutes concluded that the use of HBOCs was associated with a significantly increased risk of death and myocardial infarction based on an analysis of the available data from 13 randomized controlled trials [135].…”
Section: Regulation Of Blood Pressure After Hemorrhagic Shockmentioning
confidence: 99%